If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying onehalfx + 3 = 7 Reorder the terms: 3 + aefhlnox = 7 Solving 3 + aefhlnox = 7 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + aefhlnox = 7 + -3 Combine like terms: 3 + -3 = 0 0 + aefhlnox = 7 + -3 aefhlnox = 7 + -3 Combine like terms: 7 + -3 = 4 aefhlnox = 4 Divide each side by 'efhlnox'. a = 4e-1f-1h-1l-1n-1o-1x-1 Simplifying a = 4e-1f-1h-1l-1n-1o-1x-1
| -5x+8=-7x-16 | | 4.5=34.5-3w | | 4ln(6y-1)=36 | | x-5-10=15 | | 0.72x+0.5=0.3-0.27x+0.3 | | -5x+1=2-6x | | x+4=7.5 | | -5x+1=5x-9 | | -X+8.5=14.2 | | 3x-9=-73-5x | | forx=7 | | 8+4x=-4x+80 | | 8x+16=23 | | 4(x+1)+3x+7=52 | | -8+2x=-7x+73 | | 3(w+6)= | | (1/3)3.14*4*3^2 | | 3.4q-3.2-2.6q=-0.2q-4.8 | | X+10=7x-26 | | Since=0.48 | | 2x^2-16+20=0 | | 10=z/6-2 | | 3(x-1)+3-2x=4 | | 9x^2+7=8 | | (1/3)^3.14*4*3^2 | | 15/x=x-2 | | 8f+9=15 | | 5c+1=-1+6x | | 3(y-6)-5y= | | 8+5x=-4x+80 | | (4x+1)(x-6)=0 | | 5c(c+7)= |